2018
DOI: 10.1177/1359105318763502
|View full text |Cite
|
Sign up to set email alerts
|

‘To give is better than to receive?’ Couples massage significantly benefits both partners’ wellbeing

Abstract: This experimental study evaluated the differential effects of 'giving' and 'receiving' massage on wellbeing in healthy but stressed couples. Forty-two volunteers started the study and of these, 38 (i.e. 19 couples) completed a 3-week massage course. Emotional stress and mental clarity were assessed before and after mutual massage between each pair of adults belonging to a couple at home. While massage benefitted both parties' wellbeing within a session, critically we found no differences in wellbeing between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 22 publications
(24 reference statements)
3
22
0
Order By: Relevance
“…This aligns with a balanced view of positive psychology, which deals with both negatives and positives [45]. The expected positive outcomes of PM include increasing positive emotions, positive cognitions, positive behaviours and positive relationships [41]. Among these, the particular strength in PM is the dyadic approach in close relationships via shared positive health experiences.…”
Section: Theoretical Link Between Positive Psychology and Massagesupporting
confidence: 61%
See 4 more Smart Citations
“…This aligns with a balanced view of positive psychology, which deals with both negatives and positives [45]. The expected positive outcomes of PM include increasing positive emotions, positive cognitions, positive behaviours and positive relationships [41]. Among these, the particular strength in PM is the dyadic approach in close relationships via shared positive health experiences.…”
Section: Theoretical Link Between Positive Psychology and Massagesupporting
confidence: 61%
“…The first study to explore the effect of PM demonstrated significant improvements in mental clarity coupled with a significant reduction of emotional stress. Importantly, these effects were found for both receivers and givers of massage [41]. Similarly, the PM programme produced significant increases in mental wellbeing and perceived coping, with a strong trend toward increased relationship satisfaction also present [40].…”
Section: Positive Massagementioning
confidence: 83%
See 3 more Smart Citations